Caracterização Epidemiológica da Mortalidade Materna por COVID-19 no Brasil - Joyce Arce Alencar (2024)
Reducing maternal mortality remains a challenge for national and global health systems, aligned with the Sustainable Development Goals that seek to reduce the maternal mortality ratio to 30 per 100,000 live births. Despite the reduction of this index over the years, driven by the development of health policies, Brazil faces a growing increase in the maternal mortality ratio since 2020, due to the COVID-19 Pandemic, which had significant impacts on society as a whole. Objective: to analyze the epidemiological characterization of pregnant women and puerperal women who died from COVID-19 in Brazil in the years 2020 and 2021. Methodology: study in three stages. Ecological, retrospective and analytical study. Being the study population the pregnant women and puerperal women who died in the years 2020 and 2021 and who had confirmed diagnosis for COVID-19. Time series study of the period 2002 and 2021. Data from both were collected in the Mortality Information System, Information System on Live Births and the Brazilian Obstetric Observatory COVID-19. The data analysis used the crossing of variables of epidemiological interest through the software Statistical Package for the Social Sciences (SPSS) version 16.0. Subsequently, for the documentary study, articles were selected through the Virtual Health Library (VHL), analyzed from thematic analysis. Results: there were 19,498 cases of COVID-19 in pregnant women and postpartum women registered and 1,980 (10.15%) of these cases died. The predominant epidemiological characterization highlighted brown women, aged 30 to 39 years, with schooling from 8 to 11 years and who were in the third trimester of pregnancy. The North region prevailed with the highest maternal mortality ratio in the biennium and the second place was for the Northeast in 2020 and for the Midwest in 2021. The documentary study articles were divided into three thematic axes, maternal mortality associated with COVID-19 (36.8%), maternal and neonatal outcomes in addition to mortality (47.3%) and clinical characteristics of maternal mortality due to COVID-19 (15.7%). Final considerations: the epidemiological information represented in this study plays an essential role in the formulation by the health system of effective through the consolidation of public policies that strengthen actions aimed at women’s health, being fundamental to reduce the occurrence of irreversible and impactful outcomes for the whole society and assisting in the journey in search of achieving the Sustainable Development Goals for the reduction of maternal mortality.